Synthesis, Structural Studies, and Anticancer Properties of [CuBr(PPh3)2(4,6-Dimethyl-2-Thiopyrimidine-κS] - Bandar A. Babgi; Jalal H. Alsayari; Bambar Davaasuren; Abdul-Hamid Emwas; Mariusz Jaremko; Magda H. Abdellattif; Mostafa A. Hussien (Crystals, 2021)
CuBr(PPh3)2(4,6-dimethylpyrimidine-2-thione) (Cu-L) was synthesized by stirring CuBr(PPh3)3 and 4,6-dimethylpyrimidine-2-thione in dichloromethane. The crystal structure of Cu-L was obtained, and indicated that the complex adopts a distorted tetrahedral structure with several intramolecular hydrogen bonds. Moreover, a centrosymmetric dimer is formed by the intermolecular hydrogen bonding of the bromine acceptor created by symmetry operation 1−x, 1−y, 1−z to the methyl group (D3 = C42) of the pyrimidine–thione ligand. HSA-binding of Cu-L and its ligand were evaluated, revealing that Cu-L binds to HSA differently than its ligand. The HSA-bindings were modeled by molecular docking, which suggested that Cu-L binds to the II A domain while L binds between the I B and II A domains. Anticancer activities toward OVCAR-3 and HeLa cell lines were tested and indicated the significance of the copper center in enhancing the cytotoxic effect; negligible toxicities for L and Cu-L were observed towards a non-cancer cell line. The current study highlights the potential of copper(I)-phosphine complexes containing thione ligands as therapeutic agents.